PLASMA LEVEL OF SOLUBLE CD30 IN PEDIATRIC LIVING-DONOR LIVER TRANSPLANT PATIENT - O. P. Shevchenko; O. M. Tsirulnikova; G. A. Olefirenko; M. E. Pishchulina; I. E. Tsirulnikova; A. V. Bugrov; A. A. Andrianova; S. V. Gautier (Вестник трансплантологии и искусственных органов)
Soluble CD30 (sCD30) is a marker of T-lymphocytes activation and is used for monitoring rejection in patients after heart, lung and renal transplantation. The aim of the study was to evaluate plasma levels of sCD30 in child- ren before and after living-donor liver transplantation (LDLT) and its relationship with the postoperative course. The study included 72 children with end-stage liver disease (ESLD), aged 17 ± 11 (4–28) months before and after LDLT, 15 healthy children aged 9.9 ± 5.7 (3–21) months and 38 adult living-related liver donors, aged 37 ± 19 (18–56) years. In children with ESLD pre-transplant plasma level of sCD30 (84,9 ± 43,8 ng/ml) was significantly higher than in healthy donors and healthy children (26.4 ± 12.0 and 32.6 ± 6.9 ng/ml, resp., p < 0.01). After LDLT plasma level of sCD30 was higher in children, who had graft dysfunction at days 28–32 (108.9 ± 17.7 ng/ml) after LDLT than in children who had no graft dysfunction (40.2 ± 5.3 ng/ml, р < 0.01). In patients with graft dysfunction elevation of sCD30 concentration was observed before 2–5 days increasing of liver enzyme activity. The measurement of sCD30 concentration may be useful for monitoring of the postoperative course.